Development of BiOBr/TiO2 nanotubes electrode for conversion of nitrogen to ammonia in a tandem photoelectrochemical cell under visible light - Prita Amelia; Jarnuzi Gunlazuardi (International Journal of Renewable Energy Development, 2023)
Ammonia (NH3) is one of the important chemicals for human life. The demand for ammonia is expected to increase every year. Conventionally, the fixation process of N2 to produce NH3 in the industrial sector is carried out through the Haber−Bosch process, which requires extreme temperature and pressure conditions that consume a high amount of energy and emit a considerable amount of CO2. Therefore, it is necessary to develop alternative technology to produce ammonia using environmentally friendly methods. Many studies have developed the photo-electrochemical conversion of nitrogen to ammonia in the presence of semiconductor materials, but the resulting efficiency is still not as expected. In this research, the development of the tandem system of Dye-Sensitized Solar Cell - Photoelectrochemistry (DSSC - PEC) was carried out for the conversion of nitrogen to ammonia. The DSSC cell was prepared using N719/TiO2 nanotubes as photoanode, Pt/FTO as cathode, and electrolyte I-/I3-. The DSSC efficiency produced in this research was 1.49%. PEC cell at the cathode and anode were prepared using BiOBr/TiO2 nanotubes synthesized by the SILAR (Successive Ionic Layer Adsorption and Reaction) method. The resulting ammonia levels were analyzed using the phenate method. In this study, ammonia levels were obtained at 0.1272 µmol for 6 hours of irradiation with an SCC (Solar to Chemical Conversion) percentage of 0.0021%.